Managing Injuries and Utilizing Protein: A Literature Review on Strategies for Enhancing Athletic Performance in Modern Sports Health - Rahmatil Husni; Muhamad Sazeli Rifki; Arsil Arsil; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to assess the impact of protein utilization and injury management on enhancing athletic performance and recovery in modern sports. Utilizing a qualitative descriptive research model, the study involves a comprehensive review of literature from reputable scientific databases such as Scopus, ScienceDirect, and Google Scholar. Keywords such as "Injury Management," "Protein Utilization," and "Athletic Performance" guided the search for relevant studies. The analysis reveals that adequate protein intake and balanced nutrition are vital for muscle repair, reducing muscle damage, and accelerating recovery following injury or intense exercise. The findings emphasize that effective nutritional strategies not only support recovery but also contribute to injury prevention and overall performance improvement. Personalized nutrition plans tailored to individual needs and specific conditions, including those of athletes with spinal cord injuries or from various sports disciplines, are crucial for optimizing outcomes. The study highlights that integrating protein and nutritional strategies into training and recovery programs can significantly enhance athletic performance and reduce the risk of injuries. Effective injury management, coupled with appropriate protein utilization, plays a pivotal role in achieving better recovery rates and improving overall health. By adopting these evidence-based strategies, athletes can better meet their performance goals and enhance their overall well-being. This research underscores the importance of a comprehensive and personalized approach to nutrition and injury management in sports health, offering valuable insights for optimizing athletic training and recovery practices